(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Cyber Aggression and Abuse (CAA) is a highly structured form of digital hostility that requires a more sophisticated linguistic analysis than is provided by established psychological paradigms. The present study examines the pragmatic and linguistic factors at play in cyberbullying through the use of Speech Act Theory and Jonathan Culpeper’s Impoliteness framework. This paper employs a qualitative descriptive design and corpus-based linguistic analysis to investigate the language of offenders in their commission of purposeful face-attacks and symbolic violence through commands, expressives, and commissives. The results reveal that digital impoliteness is not monolithic but strongly constrained by platform-specific affordances. High-velocity platforms produce naked on-record impoliteness, threaded groups produce theatrical irony. Moreover, multimodal features allow for extreme negative impoliteness such as cyberflashing. In the end, understanding CAA as a set of performative language interventions provides valuable insights into how to construct more rigorous, context-aware Natural Language Processing (NLP) systems for automatic content moderation.